A comparison study between official records and self-reports : implications to health research on childhood adversity - Maia, Ângela (2011)
Background: Evidence of a relationship between experiences of maltreatment and later health outcomes has been based on cross-sectional studies using retrospective self-reports. However, many researchers view retrospective self-reports skeptically. This study compared experiences of maltreatment and other childhood adversities, identified in children through official records with self-reports obtained in late adolescence. Methods: Participants included 131 youths who had been confirmed as victims of maltreatment prior to age 13 by Child Protective Services. Findings: Emotional and physical neglect were the most prevalent experiences found in the official records: 80% and 86% respectively. However, when were assessed through self-report, only 51% of participants reported emotional neglect and 36% reported physical neglect. Only a small number of self-reports were consistent with official records (17%). Discussion: The results of the relationship between self-report of maltreatment and later health outcomes should be approached with caution when retrospective reports or official data are used alone.